Effect of Obstetrics and Gynecology Clerkship Order on National Board of Medical Examiners Scores. (October 2015) - Shvartsman, Katerina; Olsen, Cara; Zahn, Christopher
Abstract : APGO Advisor: : Sonya Erickson, MD PURPOSE: To examine the effect of rotation order on the end-of-clerkship National Board of Medical Examiners (NBME) Obstetrics and Gynecology Subject Examination scores. BACKGROUND: Integrated clerkships are intended to improve overall comprehension and critical thinking skills. At our university, a 15‐week interval is divided into 5 weeks blocks of general surgery, obstetrics and gynecology, and surgical subspecialties, in any order. During the 16th week, students take the NBME Subject Examinations for obstetrics and gynecology and surgery. METHODS: The NBME Obstetrics and Gynecology Subject Examinations scores of all students were reviewed. Rotation groups were defined by proximity to shelf exam. Group 1 completed obstetrics and gynecology first, furthest away from the exam, group 2 completed obstetrics and gynecology second, and group 3 completed obstetrics and gynecology last, closest to the test. Average shelf exam scores were compared. RESULTS: Data were obtained for 281 students (100 students in group 1, 90 in group 2, and 91 in group 3). Scores ranged from 55 to 99 with an overall mean of 72.7 and standard deviation of 7.4 (standard deviation [SD]). Mean (SD) NBME score was 72.1 (7.1) in group 1, 73.0 (7.3) in group 2, and 73.1 (7.8) in group 3. The differences were not statistically significant ( F [2, 278]=.484, P =.617). DISCUSSION: Rotation order does not affect NBME Obstetrics and Gynecology Subject Examination scores in a 15-week clerkship.